Legal regime of inventions (Eurasian Research Bulletin, 2023)
The article discusses the issues of determining the legal regime of inventions under the legislation of the Republic of Uzbekistan. The analysis of the types of inventions common in practice and their legal characteristics is carried out. The author comes to the conclusion that a unified approach to the definition of the concept and features of inventions has not yet been formed in science.